1995
DOI: 10.1016/0006-2952(95)00066-9
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin analogs: clinical application in relation to human somatostatin receptor subtypes

Abstract: receptor scintigraphy with indium-111-DTPA-D-Phel-octreotide in man: Metabolism, dosimetry and comparison with iodine-123-Tyr-3-octreotide. J Nucl Med 33: 652-658, 1992. Krenning EP, Kooy PPM, Bakker WHB, Breeman WAP, Postema PTE, Kwekkeboom DJ, Oei HY, de Jong M, Visser TJ, Reijs AEM and Lamberts SWJ, Radiotherapy with a radiolabeled somatostatin analog ['"In-DTPA-o-Phe']-octreotide: A case history. Ann NY Acad Sci 733: 496-506, 1994.Laduron PM, From receptor internalization to nuclear translocation. Biochem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 74 publications
1
27
0
1
Order By: Relevance
“…However, there are important differences between the receptor subtypes, which suggest that they may mediate different functions of the native peptide. Each receptor subtype has a distinct tissue distribution, different ligand specificities and is linked to different intracellular coupling systems in addition to adenyl cyclase (reviewed in Hofland et al, 1995). Structurally, the greatest homology is between SSTR2, SSTR3 and SSTR5 on the one hand and SSTR1 and SSTR4 on the other, and these structural homologies translate into similar pharmacological profiles (Serrano et al, 1993).…”
Section: Control Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are important differences between the receptor subtypes, which suggest that they may mediate different functions of the native peptide. Each receptor subtype has a distinct tissue distribution, different ligand specificities and is linked to different intracellular coupling systems in addition to adenyl cyclase (reviewed in Hofland et al, 1995). Structurally, the greatest homology is between SSTR2, SSTR3 and SSTR5 on the one hand and SSTR1 and SSTR4 on the other, and these structural homologies translate into similar pharmacological profiles (Serrano et al, 1993).…”
Section: Control Experimentsmentioning
confidence: 99%
“…However, it appears that the five receptor subtypes have a distinct, but overlapping, tissue distribution, unique pharmacological properties and are coupled to a number of intracellular signalling pathways, suggesting that they mediate different functions of the native peptide (Hofland et al, 1995). There is evidence that the direct growth-inhibitory effects of somatostatin are mediated, at least in part, by the activation of intracellular phosphatases (Liebow et al, 1989), and receptor subtypes 1 and 2 have been shown to be coupled to this intracellular pathway (Buscail et al, 1994(Buscail et al, -1995.…”
mentioning
confidence: 99%
“…SS binding to SSTR subtypes activates a series of second messenger systems, resulting in the inhibition of calcium channels and adenylate cyclase activity, ultimately leading to inhibition of hormone secretion (Reisine & Bell 1995, Patel 1997, 1999. Stimulation of other second messengers, such as phosphotyrosine phosphatases (PTPs), plays a role in SS-and somatostatin analogs (SSA)-mediated control of cell growth (Schally 1988, Lamberts et al 1991, Hofland et al 1995, Patel 1999, Hofland & Lamberts 2003, Florio 2008, Schonbrunn 2008. Among the SSTR, sst 3 appears to be the subtype mostly related to the pro-apoptotic and antiproliferative effects of SS and SSA (Ferone et al 2002, Hofland & Lamberts 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, small neuropeptides, such as somatostatin (SST) and gastrin releasing peptide (GRP)/bombesin (BN) analogues, labelled with g -and/or b --emitting radionuclides are investigated for their ability to bind to receptors which are overexpressed in a variety of malignant tumours [14][15][16]. The affinity of the designed chelator-peptide construct to these receptors may vary depending on the metal incorporated into the complex [17].…”
Section: Introductionmentioning
confidence: 99%